Immunohistochemical investigation of the angiogenic proteins VEGF, HIF-1α and CD34 in invasive ductal carcinoma of the breast - Maschio, Larissa Bazela; Madallozo, Bruna Bento; Capellasso, Bruno Augusto Mendonça; Jardim, Bruna Victorasso; Moschetta, Marina Gobbe; Jampietro, Juliano; Soares, Fernando Augusto; Zuccari, Debora Aparecida Pires de Campos (Elsevier, 2013)
The expression of prognostic markers in cancer has become important in diagnostic routine and research. A high mitotic rate compromises the individual cell access to oxygen and nutrients, due to reduced blood supply. Cells undertake adaptive measures such as vascular endothelial growth factor (VEGF), expressed under the control of hypoxia-inducible factor-1α (HIF-1α). CD34 is an endothelial marker which can show the presence and distribution of blood vessels. This study evaluated the presence and relative expression of VEGF, HIF-1α and CD34 using immunohistochemistry of 60 breast tumors and double staining, correlating the findings with clinical and pathological variables. High VEGF expression was correlated with low cell proliferation, lymph node-negative, smaller tumor size and patients not receiving hormone therapy. High HIF-1α expression predominated in younger (<50-year) patients, subjected to neo-adjuvant therapy and in p53-negative tumors. Absence of metastasis, radiotherapy or hormone treatment, and estrogen receptor (ER)-positive tumors showed high CD34 immunoreactivity. We suggest that the angiogenic factors VEGF, HIF-1α and CD34 are important in breast cancer progression and their abundance in breast tumors has prognostic and predictive value. Crown Copyright © 2013.
Keywords: Breast cancer; CD34; HIF-1α; Human; Immunohistochemistry; Prognostic; VEGF